Predictors of Students' Sustainable Behavior in Green Campus Programs: A Theory of Planned Behavior Approach and Student Perception Analysis at Universitas Sebelas Maret - Tiwi Utari; Maria Theresia Sri Budiastuti; Rhina Uchayani Fajarningsih (PT Keberlanjutan Strategis Indonesia, 2026)
This study examines the influence of Theory of Planned Behavior (TPB) constructs — attitude, subjective norm, and perceived behavioral control — on students’ sustainable behavior across four dimensions: pro-ecological, frugal, altruistic, and equitable, while mapping student perceptions of UI GreenMetric indicators to identify Green Campus intervention priorities at Universitas Sebelas Maret (UNS). A cross-sectional quantitative design was employed involving 163 active UNS students selected through purposive sampling, using validated questionnaires analyzed through multiple linear regression. The TPB model significantly predicted sustainable behavior overall, with attitude and perceived behavioral control as consistent significant predictors while the subjective norm showed no significant effect at the aggregate level. Predictive power varied dramatically across dimensions, from near-strong explanation in altruistic and pro-ecological behavior to near-zero in equitable behavior, revealing that sustainable behavior dimensions operate through fundamentally different psychological mechanisms, with equitable behavior appearing to function through moral value processes beyond TPB’s explanatory scope. Perception mapping identified a structural gap between institutional achievement and student experience: waste management, despite UNS ranking 4th nationally, was identified as the top student priority yet barely perceived in daily campus life, while sustainable transportation emerged as the sharpest paradox confirmed simultaneously by regression findings, behavioral self-reports, and GreenMetric rankings. These findings challenge the assumption that high institutional sustainability achievement automatically produces behavioral change among students, and call for differentiated strategies targeting infrastructure improvement, social norm reinforcement, and program communication embedded in students’ daily experience.